Microalgae biomass harvesting by electrocoagulation - Matos, Cristina T. (2013)
The use microalgae biomass for the production of biofuels has received great attention in the last decades. Microalgae biofuels could be important alternative to conventional biofuels since microalgae could be produced at high rates without the need of neither arable land, potable water or competition with food. However, the high energy intensive harvesting processes are limiting the commercial production of microalgae biofuels. In this study, Electro-Coagulation (EC) was used for harvesting the freshwater microalga Chlorella vulgaris and the marine microalga Nannochloropsis sp. The results show that EC could be an alternative to the conventional harvesting processes since it is efficient and produces good quality biomass with low energy requirements.